The Accumulation Characteristics of the Paleozoic Reservoir in the Central-Southern Ordos Basin Recorded by Organic Inclusions. (16th September 2021) - Zhu, Ruijing; Li, Rongxi; Wu, Xiaoli; Qin, Xiaoli; Zhao, Bangsheng; Liu, Futian; Zhao, Di
Abstract : The Permian tight clastic reservoir and Ordovician carbonate reservoir were developed in the central-southern Ordos Basin. This study investigated the fluid inclusion petrography, diagenetic fluid characteristics, formation process of natural gas reservoir, source rock characteristics, and reservoir accumulation characteristics of these Paleozoic strata by petrographic observations, scanning electron microscope imaging, fluid inclusion homogenization temperature, salinity, laser Raman spectrum, and gas chromatograph analyses. The results have suggested two phases of fluid inclusions in both the Permian sandstone and the Ordovician Majiagou Formation dolomite reservoirs, and the fluid inclusions recorded the history from the early thermal evolution of hydrocarbon generation to the formation, migration, and accumulation of natural gas. The early-phase inclusions show weak yellow fluorescence and recorded the early formation of liquid hydrocarbons, while the late-phase inclusions are nonfluorescent natural gas inclusions distributed in the late tectonic fractures and recorded the late accumulation of natural gas. The brine systems of the Permian and Ordovician fluid inclusions are, respectively, dominated by CaCl2 -H2 O and MgCl2 -NaCl-H2 O. The diagenetic fluids were in the ranges of medium-low temperature and moderate-low salinity. The natural gas hydrocarbon source rocks in the Ordos Basin include both the Permian coal-bearing rocks and the Ordovician carbonates. The process of the early-phase liquid hydrocarbon formation and migration into the reservoir corresponded to 220 Ma (Late Triassic). The late large-scale migration and accumulation of natural gas occurred at 100 Ma (early Late Cretaceous), which was close to the inclusion Rb/Sr isochron age of 89.18 Ma, indicating that the natural gas accumulation was related to the Yanshanian tectonic movement.